Folding of Synthetic Homogeneous Glycoproteins in the Presence of a Glycoprotein Folding Sensor Enzyme1. Issue 11 (5th February 2014) - Dedola, Simone; Izumi, Masayuki; Makimura, Yutaka; Seko, Akira; Kanamori, Akiko; Sakono, Masafumi; Ito, Yukishige; Kajihara, Yasuhiro
Abstract UDP‐glucose:glycoprotein glucosyltransferase (UGGT) plays a key role in recognizing folded and misfolded glycoproteins in the glycoprotein quality control system of the endoplasmic reticulum. UGGT detects misfolded glycoproteins and re‐glucosylates them as a tag for misfolded glycoproteins. A flexible model to reproduce in vitro folding of a glycoprotein in the presence of UGGT in a mixture containing correctly folded, folding intermediates, and misfolded glycoproteins is described. The data demonstrates that UGGT can re‐glucosylate all intermediates in the in vitro folding experiments, thus indicating that UGGT inspects not only final folded products, but also the glycoprotein folding intermediates.